"After 300 meters turn right" – the future of Russia's GLONASS and the development of global satellite navigation systems. Issue 5 (2nd September 2014) - B. Bokov, Mikhail; Edelkina, Anastasia; Klubova, Marina; Thurner, Thomas; P. Velikanova, Natalia; Vishnevskiy, Konstantin
Abstract : Purpose: – Global navigation satellite systems (GNSS) were designed to determine the exact location of objects on land, water and air for military purposes. With the opening of the satellite signal for civilian use, the technology created business opportunities for various applications. Today, satellite positioning technology is used by transporters, carriers, motorists, surveyors, builders, foresters, etc. through a wide array of devices like mobile phones or multimedia devices with built-in receiver modules. Design/methodology/approach: – This paper provides the results of a recently held foresight exercise on the future development of Russia's GLONASS system. Findings: – The foresight exercise suggested a number niche markets where the GLONASS technology could be of great use, like monitoring of buildings and construction sides or the monitoring of shipments. In addition, in the case of Russia, large-scale government-driven investment programs will be key drivers for GLONASS' growth perspectives. Originality/value: – The paper provides a comprehensive picture of the development of GNSS for civilian use until 2020.